The role of legislative reforms and supporting mechanisms in enhancing sports entrepreneurship and its impact on the labor market in Algeria - Berbache, Noureddin; Nadir, Bouslah; Mendjhi, Makhlouf; Benelbar, Said; Benredjem, Ahmed (The International tax journal, 2025)
This study aimed to explore the feasibility of establishing certain projects within the framework of sports entrepreneurship, in addition to examining the role of specialized agencies in supporting entrepreneurs. It also sought to understand the impact of legislative reforms and supportive mechanisms on enhancing sports entrepreneurship and its effects on the labor market in Algeria. The study included proposals for several possible sports projects in this field and evaluated the feasibility of some of them. The descriptive method was employed in the study. Several findings and recommendations were reached, including the importance of promoting a culture of sports entrepreneurship in Algeria and enhancing these projects at local, national, and international levels through various media outlets. The study indicated that the labor market would continue to experience stagnation in job opportunities in the absence of entrepreneurial projects, particularly in sports. The National Agency for the Support and Development of Entrepreneurship (ANADE) aims to support and develop entrepreneurial projects for project holders by providing loans to create job opportunities for youth in Algeria.